Embryonal tumor with multilayered rosettes in a teenager - Kofi Ulzen-Appiah; Kafui Patrick Akakpo (University of São Paulo, 2022)
Background: Embryonal tumor with multilayered rosettes (ETMR), NOS/C19MC- altered, is a rare and recently classified highly aggressive malignant brain tumor in the 2021 World Health Organization (WHO) classification of tumors of the central nervous system 5th edition. They are mostly diagnosed in children before the age of three years. Most of them are located in the supratentorial region. Prior to the reclassification of ETMR as a single entity, three distinct tumors, namely, embryonal tumor with abundant neuropil and true rosettes (ETANTR), ependymoblastoma (EBL) and medulloepithelioma (MEPL) were recognized. Recent studies showed that all the three entities have multilayered rosettes on morphology, sharing a common amplification of the C19MC locus at the chromosome 19q13.42 by fluorescence in situ hybridization, and highly specific immunohistochemical staining for LIN28A rendered their reclassification as a single entity. Report: A 13-year-old girl was rushed to the emergency room unconscious, with no return of spontaneous circulation after cardiopulmonary resuscitation. Autopsy revealed a left cerebellar hemisphere hemorrhagic tumor which histopathological examination revealed a multilayered ependymoblastic rosettes with abundant neuropil. The multilayered rosettes showed reactivity for vimentin but non-reactivity for pan-cytokeratin, the zones with abundant neuropil were reactive for synaptophysin consistent with a diagnosis of embryonal tumor with abundant neuropil and true rosettes now ETMR, NOS (WHO Grade 4) due to the lack of genetic testing for amplification of C19MC. Conclusion: ETMR is a highly aggressive CNS embryonal tumor with extremely poor prognosis. It should be considered in the differential diagnosis of pediatric brain tumors. Multilayered rosettes are a useful clue to histologic diagnosis.